Geotechnical Characterisation and Geoenvironmental Engineering IGC 2016 Volume 1 - Stalin, V. K.; Muttharam, M. (Lecture Notes in Civil Engineering,, 2019)
The book comprises selected proceedings of the 2016 annual conference of the Indian Geotechnical Society. The technical papers presented on the theme "Geotechnical Characterisation and Geoenvironmental Engineering" highlight the modified geotechnical properties of soil admixed industrial waste and also the characteristics of soil with different pore fluid under varying test conditions. The major topics covered are (i) characterisation of soils, rocks and synthesised materials and (ii) geoenvironmental engineering and behaviour of unsaturated soil. This book will prove a valuable reference for researchers and practicing engineers alike.